Insights into the phytochemical profiling, antidiabetic and antioxidant potentials of Lepionurus sylvestris Blume extract in fructose/streptozotocin-induced diabetic rats - Pan, Xianzhu; Olatunji, Opeyemi Joshua; Basit, Abdul; Sripetthong, Sasikarn; Nalinbenjapun, Sirinporn; Ovatlarnporn, Chitchamai (Frontiers in Pharmacology, 2024)
In this study, the antidiabetic activities of Lepionurus sylvestris Blume extract (LSB) in rats was investigated. The in vitro antidiabetic properties of LSB was evaluated using α-amylase, α-glucosidase and DPP-IV inhibitory assays, while the antioxidant assay was analysed using DPPH, ABTS and FRAP assays. Type 2 diabetes was with high-fructose/streptozotocin, and the diabetic animals were treated with LSB for five weeks. At the end of the experiment, the effects of LSB were evaluated via insulin level, lipid profile and hepatorenal function biomarkers. The level of oxido-inflammatory parameters, histopathology and insulin immunohistochemical staining in the pancreas was evaluated. Diabetic rats manifested significant increases in the blood glucose level, food/water intake, lipid profiles, hepatorenal function biomarkers, as well as a marked decreases in the body weight and serum insulin levels.Histopathological and insulin immunohistochemical examination also revealed decreased pancreatic beta cells and insulin positive cells, respectively. These alterations were associated with significant increases in malondialdehyde, TNF-α and IL-1β, in addition to significant declines in GSH, SOD and CAT activities. LSB significantly reduced blood glucose level, glucose intolerance, serum lipids, restored altered hepatorenal and pancreatic functions in the treated diabetic rats. Further, LSB showed antioxidant and anti-inflammatory activities by reducing malondialdehyde, TNF-α, IL-1β, and increasing antioxidant enzymes activities in the pancreatic tissues. A total of 77 secondary metabolites were tentatively identified in the UPLC-Q-TOF-MS analysis of LSB. Overall, these findings provides insight into the potentials of LSB as an antidiabetic agent which may be associated to the plethora bioactive compounds in the plant.